Review: Methods for Detecting Short-Chain Fatty Acids (SCFA) in Industrial and Biological - Hutri Puspita Sari; Aster Rahayu; Dhias Cahya Hakika; Zahrul Mufrodi; Gita Indah Budiarti (Universitas Nusa Bangsa, 2025)
Industrial and biological wastes are major contributors to environmental pollution and contain high levels of organic matter that can generate short-chain fatty acids (SCFA) through microbial fermentation. SCFAs are important not only as bioenergy precursors in industrial waste management but also as key biomarkers of gut microbiota activity in biological samples. This review provides a comparative analysis of analytical methods used to detect SCFAs in both industrial and biological matrices, focusing on High-Performance Liquid Chromatography (HPLC), Gas Chromatography with Flame Ionization Detection (GC-FID), and Liquid Chromatography–Tandem Mass Spectrometry (LC-MS/MS). The findings reveal that HPLC—particularly Ion-Exclusion HPLC—is most effective for analyzing complex industrial waste samples such as waste-activated sludge (WAS) and palm oil mill effluent (POME), whereas GC-FID is more suitable for volatile-rich wastes like vinasse. Meanwhile, LC-MS/MS demonstrates exceptional accuracy and sensitivity for biological matrices such as feces, serum, and urine, allowing detection at ultra-trace concentrations. These insights underscore the need for optimized, waste-specific detection techniques to enhance environmental monitoring, waste valorization, and health-related SCFA research. Future studies should focus on developing rapid, cost-effective, and IoT-integrated detection systems to support real-time monitoring of both industrial and biological wastes.